Mutations of glucocerebrosidase gene and susceptibility to Parkinson's disease: An updated meta-analysis in a European population. (21st April 2016) - Zhao, F.; Bi, L.; Wang, W.; Wu, X.; Li, Y.; Gong, F.; Lu, S.; Feng, F.; Qian, Z.; Hu, C.; Wu, Y.; Sun, Y.
Highlights: The results indicated GBA mutations were associated with increased PD risk in the European population. Patients with early-onset were more likely to carry GBA mutations than those with late-onset. Moreover, N370S and L444P were found to increase PD risks. Abstract: This meta-analysis aims to investigate the association between mutations of glucocerebrosidase ( GBA ) gene and susceptibility to Parkinson's disease (PD) in a European population. Several electronic databases were extensively searched. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the association. In total, fourteen published papers screening L444P, N370S and other GBA variants were identified. The GBA mutations were significantly associated with PD in the European population. Subgroup analysis stratified by the age of onset (AAO) revealed that the association between GBA mutations and PD existed in the patients with age at onset ⩽50 years but did not exist in the patients with age at onset >50 years. Furthermore, the associations between N370S, and L444P with PD were also analyzed to explore the roles of the two most frequent GBA mutations in the development of PD. The results showed that significant associations between N370S, and L444P with PD were observed, respectively. Overall, the study supported that GBA mutations were a risk factor for PD in the European population. Patients with early-onset were more likely to carry GBA mutations than those with late-onset. Moreover, both L444P and N370S were associated with increased PD risk.